Investigation of direct biodiesel production from wet microalgae using definitive screening design - Felix, Charles B. (Animo Repository, 2019)
Microalgae are regarded as a notable alternative fuel owing to the growing concerns for energy supply and climate change. However, there are still some major setbacks that need to be addressed to make the said resource promising to stakeholders. One of these is the drying process, which accounts for the majority of the energy input in biodiesel production. To make it more competitive against fossil-based fuels, new strategies in producing microalgal biofuels need to be developed. One promising thermo-chemical conversion process is the direct or in-situ transesterification. Literature suggests that subjecting the reactants at a subcritical state can eliminate the use of certain catalysts and tolerate certain amounts of moisture and free-fatty acid contents. A definitive screening design of experiment was adapted to generate preliminary observations regarding the effects of temperature, time, and solvent concentration on the reactive-extraction process. Optimum operational settings of the three variables which maximizes the biodiesel yield and minimizes the process power consumption were predicted and validated accordingly. © 2019 The Authors. Published by Elsevier Ltd. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/) Peer-review under responsibility of the scientific committee of ICAE2018 - The 10th International Conference on Applied Energy.